2019
DOI: 10.3390/smartcities2020010
|View full text |Cite
|
Sign up to set email alerts
|

People-Centric Service Intelligence for Smart Cities

Abstract: In the era of big data, smart cities have become a promising prospect for governments, citizens, and industrials. Many ideas and their derived systems for smart cities depend on big data for achieving a goal of data intelligence. However, there is an urgent transformation trend from data intelligence to service intelligence in the vision of smart cities due to the living requirements of citizens. People-centric service intelligence in smart cities has to support the realization of people’s needs within urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 73 publications
0
27
0
1
Order By: Relevance
“…The dynamic process can be found in Figure 4, by judging the burst keyword order such as: choice, smart growth, urban form, density, design, transportation. Just as some researchers said, there was an urgent transformation trend from data intelligence to service intelligence in the vision of smart cities due to the living requirements of citizens [46]. Keyword bursts also showed that the theme of the study changed quickly as time went on, and many branches of smart city research were synchronously thriving.…”
Section: Co-keyword and Keyword Citation Bursts Analysismentioning
confidence: 99%
“…The dynamic process can be found in Figure 4, by judging the burst keyword order such as: choice, smart growth, urban form, density, design, transportation. Just as some researchers said, there was an urgent transformation trend from data intelligence to service intelligence in the vision of smart cities due to the living requirements of citizens [46]. Keyword bursts also showed that the theme of the study changed quickly as time went on, and many branches of smart city research were synchronously thriving.…”
Section: Co-keyword and Keyword Citation Bursts Analysismentioning
confidence: 99%
“…Xu suggests that based on the trend of richness and extensiveness of social network development, the administration is called upon to use intelligent means to collect multiple types of data in the community, to implement proactive innovation in the administration, and to actively experience the reasonable ideas and needs of community residents to expand the coverage of public services [7]. Bibri and Krogstie suggest that the smart network governance approach makes community governance democratic and effective [8].…”
Section: Related Studiesmentioning
confidence: 99%
“…The paradigm of the world's smart cities is the primary focus of the data. While data collection is a necessary process, the assignment of data content and in particular the focus on the human factor should not be forgotten [14]. The basic motivation for the proper management of any area of a smart city is to provide its citizens with a people-oriented model that acknowledges and specifies the distinctive characteristics of culture, stakeholder satisfaction and generally accepted and applied equality [14].…”
Section: Building Smart City Approachesmentioning
confidence: 99%